BENEFITS OF MANAGEMENT GAMES IN DISPLAYS PERFORMANCE STUDENT AT ILEARNING EDUCATION - Apriani, Desy; Harahap, Eka Purnama; Wardhani, Paramitha Kusuma (UNIVERSITAS RAHARJA, 2021)
The development of learning in education has now increased. As time goes on, technology has grown rapidly. With the development of technology today can help the learning process. One example of technological advancement in education is E-Learning. E-Learning provides the convenience of lecturers and students in distance learning so that learning runs effectively and efficiently. In an effort to improve the quality of education in Indonesia, Raharja University has implemented an online learning system called iLearning. But iLearning's online learning system has not been the maximum, there are some students who have not been active in the classroom as the lecture took place and there are still students who are late working on the assignment given. To improve the performance of students while in the classroom and to perform timely assignments lecturers apply a method of gamification. Students will earn points when working on an assignment that has been given by the lecturer. The earning points are listed on the iDu Dashboard in order to provide motivation for students to do other tasks and compete with classmates. The methods used to address these problems include SWOT analysis methods, Literature Review, and Unified Modelling Language (UML) as a modeling design. This research aims to improve student performance in the process of teaching and learning activities.